2022
DOI: 10.1186/s13287-022-02824-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from hair follicle-derived mesenchymal stromal cells: isolation, characterization and therapeutic potential for chronic wound healing

Abstract: Background Mesenchymal stromal cells (MSCs) and their extracellular vesicles (MSC-EVs) have demonstrated to elicit immunomodulatory and pro-regenerative properties that are beneficial for the treatment of chronic wounds. Thanks to different mediators, MSC-EVs have shown to play an important role in the proliferation, migration and cell survival of different skin cell populations. However, there is still a big bid to achieve the most effective, suitable and available source of MSC-EVs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 97 publications
(91 reference statements)
0
29
0
Order By: Relevance
“…P3 to P6 DPCs were cultured in 100-mm dishes until 80% con uence, changing the culture medium with DMEM/F12 containing exosome-free FBS. After 48 h culture, the DPCs culture supernatants were harvested for exosome isolation by differential centrifugation/ ultracentrifugation techniques [30]. The supernatants went through 300×g for 10 min, 2,000×g for 10 min, and 10,000×g for 30 min to remove cell debris and middle-large extracellular vesicles.…”
Section: Isolation and Identi Cation Of Dpc-exosmentioning
confidence: 99%
“…P3 to P6 DPCs were cultured in 100-mm dishes until 80% con uence, changing the culture medium with DMEM/F12 containing exosome-free FBS. After 48 h culture, the DPCs culture supernatants were harvested for exosome isolation by differential centrifugation/ ultracentrifugation techniques [30]. The supernatants went through 300×g for 10 min, 2,000×g for 10 min, and 10,000×g for 30 min to remove cell debris and middle-large extracellular vesicles.…”
Section: Isolation and Identi Cation Of Dpc-exosmentioning
confidence: 99%
“…Up to now, exosomes from various cell sources have been used to promote wound healing in diabetes. Stem cells are the most studied, including adipose stem cells (ADSCs) ( 11 , 17 , 28 , 31 , 35 , 38 , 40 47 ), bone marrow mesenchymal stem cells (BMSCs) ( 15 , 16 , 23 , 26 , 32 , 33 , 37 , 44 , 48 51 ), human umbilical cord-derived mesenchymal stem cells (hUCMSCs) ( 27 , 52 , 53 ), synovium mesenchymal stem cells (SMSCs) ( 18 , 21 ), gingival mesenchymal stem cells (GMSCs) ( 39 ), human urine-derived stem cells (USCs) ( 22 ), menstrual blood-derived mesenchymal stem cells (MenSCs) ( 36 ), placental mesenchymal stem cells (PMSCs) ( 54 ), human endometrial stem cells (hEnSCs) ( 34 ), hair follicle-derived mesenchymal stromal cells ( 55 ), epidermal stem cells (ESCs) ( 56 , 57 ). Other cells, like fibrocytes ( 58 ), human umbilical cord blood endothelial progenitor cells ( 19 , 59 ), human umbilical cord blood mononuclear cells (hUCBMNCs) ( 30 ), macrophages ( 24 ), human amniotic epithelial cells ( 25 ), dermal fibroblasts (DFs) ( 14 ), M2 macrophages ( 60 ), human umbilical vein endothelial cells (HUVECs) ( 61 ), also were used for exosome isolation.…”
Section: How To Maximize the Therapeutic Effect Of Exosomesmentioning
confidence: 99%
“…Enhanced wound healing with ASC-Ex was associated with decreased inflammation, augmented wound cell proliferation, stimulating angiogenesis, and inducing M2 macrophage polarization. Heras et al [ 41 ] reported increased angiogenesis and human dermal fibroblasts proliferation and migration, in vivo, with exosomes isolated from hair follicle-derived MSCs (HF-MSCs) and adipose tissue-derived MSCs (AT-MSCs). Another study by Gondaliya et al reported enhanced collagen deposition, angiogenesis, and re-epithelialization in diabetic wounds with MSC-derived exosomes loaded with miR-155 inhibitor in a mouse model [ 42 ].…”
Section: Stem-cell Derived Exosomes and Combinational Strategies To E...mentioning
confidence: 99%